The Concept and Essence of Administrative and Legal Protection of Tax Relations (Law and Safety, 2019)
The concept and essence of administrative and legal protection of tax relations have been considered. It has been emphasized that the study of general theoretical ideas about the correlation between the concepts of legal security and legal protection will contribute to solving the tasks of the research. The provisions on the correlation of legal security and legal protection in the whole and as a part have been supported. The author has established peculiarities of administrative and legal protection compared with other types of legal protection of public relations: such activity is carried out by public administration agencies through administrative and legal means, including coercive ones. The essential components of administrative and legal protection, which should form the basis of its definition, include: prevention of negative phenomena; detection of possible violations; overcoming harmful consequences (restoration of violated rights); maintaining stable legal relations; prosecuting persons who encroach on the protected object.The author has emphasized on the peculiarities of the purpose of using the means of administrative and legal protection of tax relations – protection of public interests in the field of taxation, as an organic and balanced combination of public and private interests, the satisfaction of which contributes to the sustainable development of society.It has been found out that the content of administrative protection of a particular object is revealed through its means and measures. The analysis of sectoral studies has allowed to establish the following feature of administrative and legal protection measures: they are carried out by means of service nature, the list of which differs depending on the object of administrative legal protection, control and supervision, as well as by applying measures of administrative coercion.The need for a two-vector consideration of administrative and legal protection means has been emphasized: their impact is directed both on the taxpayer and on the controlling agencies (revenue and fees agencies).
Keywords: administrative and legal security; administrative and legal protection; tax relations; administrative and legal means; administrative coercion